Population Pharmacokinetic of Epidural Sufentanil in Labouring Women: A Multicentric, Prospective, Observational Study - Nie Y; Sun X; Cao R; Tang S; Zhou Q; Zhou M; Chen Z; Huang S (Drug Design, Development and Therapy)
Yuyan Nie,1,* Xingfeng Sun,1,* Rong Cao,2 Songjiang Tang,3 Qun Zhou,4 Min Zhou,5 Zuolei Chen,6 Shaoqiang Huang1 1Department of Anesthesiology, Obstetrics and Gynecology Hospital of Fudan University, Shanghai, People’s Republic of China; 2Department of Anesthesiology, Chengdu Women’s and Children’s Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 3Department of Anesthesiology, the First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, People’s Republic of China; 4Department of Anesthesiology, Jiangxi Maternal and Child Health Hospital, Nanchang, People’s Republic of China; 5Department of Anesthesiology, Fujian Provincial Maternity and Children’s Hospital, Fuzhou, People’s Republic of China; 6Department of Anesthesiology, the Affiliated Hospital of Qingdao Binhai University, Qingdao, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shaoqiang Huang, Department of Anesthesiology, Obstetrics and Gynecology Hospital of Fudan University, Shanghai, 200090, People’s Republic of China, Tel/Fax +86-021-33189900, Email drhuangsq@163.comPurpose: The effects of sufentanil-ropivacaine combination on the parturient women and the course of labor have been well documented. However, there is little information regarding the time-dependent pharmacokinetic characteristics of sufentanil after epidural administration in laboring women. We aimed to develop a population PK model for epidural sufentanil in laboring women to evaluate the sufentanil placental transfer quantitatively.Patients and Methods: Forty-one participants who underwent epidural labor analgesia were recruited into this study. Patients received a continuous epidural infusion of sufentanil 0.3 μg/mL with ropivacaine 0.1%. Maternal venous blood samples and umbilical venous blood samples were collected for population PK analysis. The trends of sufentanil blood concentrations in the mothers and umbilical cord were predicted by the model.Results: Sufentanil disposition after continuous epidural administration in laboring women followed a two-compartment pharmacokinetic model. The estimated sufentanil central clearance (CL), central volume of distribution (V1), clearance between central compartment and umbilical cord compartment (CL2), and umbilical cord volume of distribution (V2) were 176 L/h, 519 L, 0.0134 L/h, and 0.187 L. The absolute level of sufentanil in placental circulation is low after epidural administration. A slow decline in placental sufentanil concentration was predicted by the final PK model after epidural infusion was discontinued.Conclusion: A slow decline in placental sufentanil concentration is predicted by the final two-compartment PK model after epidural infusion was discontinued. This suggests that very large doses of epidural sufentanil should be avoided during labor analgesia.Trial Registration: https://www.chictr.org.cn, No: ChiCTR1800018810.Keywords: pharmacokinetic, sufentanil, epidural, labour, pain